Molecular phylogenetic diversity in the widespread lizard Cercosaura ocellata (Reptilia: Gymnophthalmidae) in South America. Issue 6 (2nd November 2017) - Sturaro, Marcelo José; Avila-Pires, Teresa C. S.; Rodrigues, Miguel T.
Abstract : For a long time, Cercosaura ocellata was considered polytypic, with three subspecies: C. ocellata ocellata, C. ocellata petersi and C. ocellata bassleri . Recently, C. ocellata bassleri was elevated to full species, based on analysis of a few molecular samples from Peru. This species complex is widely distributed in South America, occurring in Amazonia, Cerrado, Atlantic forest and Pampa biomes. The monophyly and species diversity of C. ocellata are still unstudied. Here, we infer phylogenetic relationships and species diversity of this group analysing 2326 base pairs of three mitochondrial (12S, 16S, and ND4) and one nuclear ( c-mos ) genes. Our taxon sampling of 115 specimens includes 72 samples of C. ocellata and sequences of other Cercosaura species and closely related Cercosaurinae. Maximum likelihood phylogenetic analysis recovered the monophyly of Cercosaura and that of C. ocellata with strong support. Our analyses suggest that C. ocellata is a complex of cryptic species, which possibly started diversifying in Amazonia.